(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2025)
The article examines the issues of improving the quality of internal audit work in the Republic of Uzbekistan based on international standards. The aim of the scientific work is to develop methodological and practical recommendations for the qualitative organization and implementation of internal audit work in the Republic of Uzbekistan.